2017
DOI: 10.1080/14767058.2017.1330882
|View full text |Cite
|
Sign up to set email alerts
|

Surgical site infection after cesarean delivery: incidence and risk factors at a US academic institution

Abstract: Several patient and surgical variables are associated with increased rate of SSI after CD. Identification of risk factors for SSI after CD is important for targeted implementation of quality improvement measures and infection control interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
37
3
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 37 publications
9
37
3
4
Order By: Relevance
“…e study also showed giving birth by CD at term was 98.1% protective ((AOR � 0.019, 95% CI: (0.001-0.291))) for the incidence of SSI compared to that of postterm deliveries. Even though direct association between preterm delivery and the outcome variable could not be found in this study, it agrees with studies in the USA and Israel that labouring at term can protect infection by avoiding complications of preterm labour such as hastened labour [16,17].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…e study also showed giving birth by CD at term was 98.1% protective ((AOR � 0.019, 95% CI: (0.001-0.291))) for the incidence of SSI compared to that of postterm deliveries. Even though direct association between preterm delivery and the outcome variable could not be found in this study, it agrees with studies in the USA and Israel that labouring at term can protect infection by avoiding complications of preterm labour such as hastened labour [16,17].…”
Section: Discussionsupporting
confidence: 85%
“…e rate, however, might be underestimated due to a significant number of lost participants. e rate, 15.1%, is significantly high compared to the results of studies done in Polish hospital, US academic institution, Israel health institution, ai-Myanmar border hospital, a hospital in Oman, two hospitals in Libya, three sub-Saharan African countries, and Tanzania which showed an incidence rate of 0.5%, 5.5%, 3.7%, 6.2%, 2.6%, 2.53-3.07%, 7.6%, and 10.9%, respectively [6,[16][17][18][19][20][21][22][23]. is difference might be due to a difference in SSI definition, distribution of risk factors among the studied group, study time, socioeconomic status, and healthcare delivery system.…”
Section: Discussionmentioning
confidence: 97%
“…This bias has been eliminated by including in the control group only patients without history of infection or the use of antibiotics until 30th postpartum day, apart from prophylaxis. Risk factors well documented in the literature, such as emergency cesarean section, duration of ruptured membranes, duration of surgery, excessive vaginal manipulation, obesity, and surgical risk must be analyzed for prophylaxis antibiotic treatment (7)(8)(9)(10)(11)(12)(13).…”
Section: Discussionmentioning
confidence: 99%
“…Patients' demographic data was retrospectively collected through an analysis of patient medical charts. Factors were identified as important data collection points following a review of related literature and so that NHSN risk indexes could be generated [9][10][11][12][13]. The following factors were recorded: age of patient, gestational age at time of operation, nature of caesarean section (emergency or elective), American Society of Anesthesiologists (ASA) score, wound class, if prophylactic antibiotics were used, if the patient experienced premature rupture of membranes (PROM) or had a predisposing illness, and length of procedure from cut to close.…”
Section: Methodsmentioning
confidence: 99%